Excimer laser coronary angioplasty application in acute myocardial infarction - Ilkay, E; Karaca, I; Akbulut, M; Kilicoglu, AE; Ozbay, Y; Yavuzkir, M; Arslan, N (Medimond S R L, 2001)
The studies about the excimer laser coronary angioplasty application in acute myocardial infarction are very limited. ELCA and stent implantation were applied to 8 male, 2 female (n=10) patients with AMI. 1.7 vitesse Cos catheter for 7 patients, 1.4 vitesse cos for 3 patients were used at 45/25 frequency with mean 10+/-3 lasing. Thrombi were lysed in all cases without distal embolism. In 2 cases (% 20) type B dissection was occurred. Stents were implanted at 12 atmosphere in all cases. ST segment resolution was greater than % 70 in all cases. The patients were discharged at fifth day with the prescription of clopidogrel, diltiazem, aspirin and atorvastatin was added in 3 patients. The patients were asymptomatic at the end of 6 month follow up; control angiography was made to 7 patients and stents were open and perfusion sintigraphy of other 3 patients were normal. In conclusion, it seems that ELCA can be used in the lysis of fresh thrombus in AMI. This small trial may be important to initiate the large scale randomised trials.
4th International Congress on Coronary Artery Disease -- OCT 21-24, 2001 -- PRAGUE, CZECH REPUBLIC
Keywords: Immediate Angioplasty; Thrombolytic Therapy; Balloon Angioplasty; Stent Implantation; Rates